+0  
 
0
130
1
avatar

\(\frac{\left(a+b\right)^n}{b^n}=\left(1+\frac{a}{b}\right)^n\)

((a+b)^n)/(b^n) = (1+a/b)^n

Guest Mar 19, 2018
edited by Guest  Mar 19, 2018

Best Answer 

 #1
avatar+7324 
+3

\(\begin{array}\ &&\frac{(a+b)^n}{b^n} \\ =&&\big(\frac{a+b}{b}\big)^n \\ =&&\big(\frac{b+a}{b}\big)^n \\ =&&\big(\frac{b}{b}+\frac{a}{b}\big)^n \\ =&&\big(1+\frac{a}{b}\big)^n \\ \end{array}\)

hectictar  Mar 19, 2018
 #1
avatar+7324 
+3
Best Answer

\(\begin{array}\ &&\frac{(a+b)^n}{b^n} \\ =&&\big(\frac{a+b}{b}\big)^n \\ =&&\big(\frac{b+a}{b}\big)^n \\ =&&\big(\frac{b}{b}+\frac{a}{b}\big)^n \\ =&&\big(1+\frac{a}{b}\big)^n \\ \end{array}\)

hectictar  Mar 19, 2018

38 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.